The m6A Methylation-Regulated AFF4 Promotes Self-Renewal of Bladder Cancer Stem Cells. (2nd July 2020) - Gao, Qian; Zheng, Jin; Ni, Zegui; Sun, Pengli; Yang, Congcong; Cheng, Maosheng; Wu, Mingqing; Zhang, Xiuhong; Yuan, Lin; Zhang, Yingyin; Li, Yang
Abstract : The dynamic N 6 -methyladenosine (m 6 A) modification of mRNA plays a role in regulating gene expression and determining cell fate. However, the functions of m 6 A mRNA modification in bladder cancer stem cells (BCSCs) have not been described. Here, we show that global RNA m 6 A abundance and the expression of m 6 A-forming enzyme METTL3 are higher in BCSCs than those in non-CSCs of bladder cancer (BCa) cells. The depletion of the METTL3 inhibited the self-renewal of BCSCs, as evidenced by decreased ALDH activity and sphere-forming ability. Mechanistically, METTL3 regulates the m 6 A modification and thereby the expression of AF4/FMR2 family member 4 (AFF4), knockdown of which phenocopies the METTL3 ablation and diminishes the tumor-initiating capability of BCSCs in vivo . AFF4 binds to the promoter regions and sustains the transcription of SOX2 and MYC which have critical biological functions in BCSCs. Collectively, our results demonstrate the critical roles of m 6 A modification in self-renewal and tumorigenicity of BCSCs through a novel signaling axis of METTL3-AFF4-SOX2/MYC.